Inovasi Pengelolaan Pusat Kegiatan Belajar Masyarakat (PKBM) : Peningkatan Kualitas Kelembagaan PKBM di Kabupaten Bandung - Ansori Ansori; Dinno Mulyono; Tiffany Estherlita; Furqon Nulhakim; Dadang Hermawan (Universitas Majalengka, 2024)
The Community Learning Center (PKBM) plays a vital role in providing educational access to communities not reached by formal institutions. However, challenges in managing and institutional management of PKBM often affect the quality of educational services. This research aims to enhance the institutional management quality of PKBM in Bandung Regency through a workshop titled